Bergamot Juice Extract Inhibits Proliferation by Inducing Apoptosis in Human Colon Cancer Cells - Visalli, Giuseppa; Ferlazzo, Nadia; Cirmi, Santa; Campiglia, Pietro; Gangemi, Sebastiano; Di Pietro, Angela; Calapai, Gioacchino; Navarra, Michele (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Colorectal cancer (CRC) is a leading cause of cancer mortality in the industrialized world, second to lung cancer. A lot of evidences highlight that a diet rich in fruits and vegetables may reduce the risk of some types of cancer including CRC. In this study we demonstrate that Citrus bergamia juice extracts (BJe) reduces CRC cell growth by multiple mechanisms. Low BJe concentrations inhibit MAPKs pathway and alter apoptosis-related proteins, that in turn induce cell cycle arrest and apoptosis in HT-29 cells. Instead, high concentrations of BJe induce oxidative stress causing DNA damage. Our study highlights the role of BJe as modulator of cell apoptosis in CRC cells and strengthens our previous hypothesis that the flavonoid fraction of bergamot juice may play a role as anti-cancer drug.
Keywords: Citrus bergamia